Pengaruh Brand Ambassador, Brand Image dan Persepsi Harga Terhadap Keputusan Pembelian Produk Kosmetik Emina - Hana Selfiana; Retno Susanti (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to analyze the significance of the influence of brand ambassadors, brand image and price perceptions on purchasing decisions for Emina cosmetic products in Surakarta. This research is a survey with data types using qualitative and quantitative data. Data sources use primary data and secondary data. The population in this research are all consumers who use Emina products in Surakarta. The total research sample was 100 people with a sampling technique using purposive sampling. Data analysis uses descriptive analysis, multiple linear regression test, t test, F test and coefficient of determination test. The research results show that brand ambassadors have a significant influence on purchasing decisions for Emina cosmetic products in Surakarta, brand image has no significant influence on purchasing decisions for Emina cosmetic products in Surakarta and price perceptions have a significant influence on purchasing decisions for Emina cosmetic products in Surakarta. The F test results show a calculated F value of 38.275 with a significance value (p-value) of 0.000 < 0.05. The coefficient of determination test result (adjusted R2) is 0.530, meaning that the contribution of the independent variables to the dependent variable is 53%.